Pengaruh geometri penampang kampas rem cakram terhadap getaran dan indikasi squeal yang muncul saat pengereman pada molina uns - Rifai Prima Alazhar; Didik Djoko S; Eko Prasetyo Budiana (Jurnal Teknik Mesin Indonesia, 2016)
Mechanical Engineering Department of Sebelas Maret University participated on the development of a national electric car (Molina UNS). One of the main components of this car is the brake system. Molina UNS use disc brakes type for all wheels. In this brake type, squeal can arise in the form of disturbance. Therefore, this study aims to determine the dynamic characteristic of disc brake during braking and the effect of brake lining cross-section geometry to brake squeal occurrence. Analysis were performed with the finite element simulation using ANSYS 14.5 software. The pressure of 0,6 MPa is given on lining, disc rotation at 5 rad/s, and friction coefficient is 0,405. Geometry variation of this simulation are brake lining without slot, single slot, double slot, and chamfered. Eigenvalues of simulation results extracted on the frequency between 0 and 13 kHz. The results show the unstable vibration mode that potentially squeal on the configuration I, II, III, IV sequentially occurs at frequencies 8769 Hz, 8713 Hz, 11737 Hz and 11460 Hz. Most of the unstable vibration modes became twisting and bending moment on the lining. Brake lining with chamfered configuration has the smallest squeal potential.